KAJIAN EFISIENSI UNIT PROTOTYPE PEMBANGKIT LISTRIK BERBASIS KONVERSI SAMPAH PLASTIK POLYPROPYLENE MENGGUNAKAN BAHAN BAKAR TEMPURUNG KELAPA PADA REAKTOR PIROLISIS - Zurohaina, Zurohaina (Politeknik Negeri Sriwijaya, 2018)
Based on Kementerian Lingkungan Hidup dan Kehutanan (KLHK) data declares that the total waste in Indonesia, 2019 will reach 68 million tons and plastic waste is estimated to reach 9.52 million tons or 14% of existing waste total. Indonesia is ranked second in the world production plastic waste into the sea that reached 187.2 million tons after China reach 262.9 million tons. The research is about the process of pyrolysis of plastic waste into liquid fuel with polypropylene as a raw material usage. Pyrolysis process decomposes into shorter hydrocarbon chains. Decomposition occurs due to the thermal energy system provides over the energy that binds to hydrocarbon chain of molecules. Pyrolysis is done in prototype of plastic waste power plant unit using coconut shell as its fuel. Liquid fuels pyrolysis products are then used as a fuel generator to convert into electrical energy with a maximum load of 900 watt. The result of this research is obtained by effiency of cylce is 39.26%.